H1N1 infection reduces glucose level in human U937 monocytes culture - Motawi, Tarek K.; Shahin, Nancy Nabil; Maghraby, Amany Sayed; Kirschfink, Michael; Nadeem Abd-Elshafy, Dina; Awad, Kareem; Bahgat, Mahmoud Mohamed (Viral immunology, 2020)
Infection with influenza A (H1N1) virus contributes significantly to the global burden of acute respiratory diseases. Glucose uptake and metabolic changes are reported in different cell types after infections with different virus types, including influenza A virus. Alteration of glucose metabolism specifically in immune cells has major health consequences. The aim of this study was to monitor glucose concentration in unstimulated and stimulated U937 human monocytes with infectious or heat inactivated H1N1 or Staphylococcus aureus or in nonpathogenically stimulated monocytes with phorbol-12-myristate-13-acetate. Stimulated or unstimulated U937 human monocytes were subjected to H1N1 infection for different time points and the glucose profile in the growth medium was measured post infection. Results showed that regardless to whether the initial stimuli on U937 cells were of pathogen or nonpathogen origins, challenge infection by H1N1 causes a significant reduction of glucose levels 36 h post infection. In conclusion, H1N1 infection has a direct effect on the glucose uptake of U937 cells in vitro. This effect can be related to either H1N1 infection or cell differentiation status that might occur due to the exerted stimuli.
Gesehen am 23.06.2021